Pharmacokinetic profile of oral firocoxib in the koala (Phascolarctos cinereus) - Amanda June Shapiro; Benjamin Kimble; Frances Hulst; Kimberly Vinette Herrin; Caroline Marschner; Chien-Jung Chen; Merran Govendir (PLoS ONE, 2025)
The pharmacokinetic profile of firocoxib administered orally at 5 mg/kg as a single dose to three mature koalas of each sex is described. After single dose administration, the harmonic means for maximal plasma concentration (Cmax), time to reach Cmax (Tmax) and elimination half-life (t1/2) were 79.2 ng/mL, 3.69 h, and 5.01 h, respectively. Males exhibited a higher Cmax than females (217.4 vs 48.4 ng/mL), suggesting greater oral absorption, while females had a slower elimination (t1/2: 5.87 h vs 4.38 h in males), however these sex differences were not significant. After a wash-out period, the same dose was administered every 12 h, on six occasions to the same koalas. With repeat dosing, females had higher trough concentrations at 24 and 48 h, and 12 h after the last dose, compared to the males. No observable adverse effects were evident in any of the koalas following repeat dosing. The target plasma concentration was approximately 100 ng/mL based on in vitro studies in other species to inhibit 80% of cyclooxygenase-2 activity (inhibitory concentration 80 [IC80]). During single firocoxib administration, this plasma concentration was attained only in the males and not in the females. Two unidentified metabolites were also observed in the chromatograms. Acknowledging the lipophilic nature of firocoxib and that it is therefore likely to persist in animals’ tissues longer than in plasma, firocoxib appears a useful nonsteroidal anti-inflammatory drug for the koala. The oral dose of 5 mg/kg twice a day for a maximum of six doses appears safe for mature male koalas. The data presented here suggests that mature females may require a higher dose (perhaps double the dose i.e., i.e., 10 mg/kg). Until further studies confirm the sex differences in pharmacokinetic profile of firocoxib and safety of higher doses in female koalas, a once daily administration of a higher dose is suggested.